Investigating Earnings Management on the Readability of Financially Troubled Indian Firms - Sweta Tiwari; Chanchal Chatterjee (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: The present study explores the impact of earnings management and ownership concentration on readability of annual reports of the financial statement of distressed Indian firms. Design/Methodology/Approach: The study uses multiple regression for analysis on a sample of 545 Management Discussion and Analysis sections of the annual report of 208 Indian financially distressed publicly traded firms for the period 2014 - 2021. Research findings: The present study reports that highly distressed Indian firms produce less readable financial disclosure. Theoretical contribution/Originality: To the best of the authors’ knowledge, this is the first study to examine the effect of earnings management and ownership pattern on the readability of financial disclosures of financially distressed Indian firms. Practitioner/Policy implication: The findings of the study have significant implications for investors, regulators and policymakers.